Stock prices of weapon companies and political conflict. - Ho, Clarrisa Yen Yee. (2010)
This paper studies the empirical relationship between political conflict and the stock rices of arms-producing companies. This topic is important as we seek to provide a general explanation of the benefits to arms-producing companies in relation to worldwide conflicts. We focus on the ten largest arms-producing companies listed on the SIPRI Top 100 for 2007, and conduct an event study on this relationship. We find that 3 out of the 10 companies display significant abnormal returns. This finding is corroborated by results from regressions on raw returns and cumulative abnormal returns around a 5-day window. We gather that conflict date and intensity show opposing effects, with positive returns for conflict intensity dominating for the 3 significant companies in the top 10. This interesting finding could be due to countries being embroiled in longstanding conflicts, hence the intensification of the conflict affects the demand for arms more than an onset of a new conflict would. We interpret our findings in the light of rampant corruption and bribery in the industry, and a merger policy that sparked off a wave of change in the defense industry landscape in 1993. We also recognize the limitations we face in the course of our study.